Peningkatan Fungsi Kognitif Lansia Dengan Terapi Modalitas Senam Otak (Brain Gym) Pada Lansia Kelompok Prolanis - Ariesti, Ellia; Sutiyarsih, Emy; Sulartri, Anastasia Sri; Diatanti, Narita (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Introduction: The elderly population is increasing in number. This is a reality that cannot be avoided. The higher the elderly population, the more elderly people will need care. The increase in the prevalence of dementia follows an increase in the elderly population. Cognitive disorders in the elderly, if not treated properly, will affect daily living activities and the overall health of the elderly. One effort to prevent cognitive decline due to aging is by doing sports or physical exercise. Objective: The purpose of this service was to increase the knowledge and empowerment of the elderly in the application of Brain Gym Modality Therapy as an effort to improve the cognitive function of the elderly in the Prolanis Group of the Tajinan Health Center, Malang Regency Method: Community service was carried out in the form of training for the Prolanis Group at the Tajinan Health Center, Malang Regency with material related to brain exercise modality therapy to improve the cognitive function of the elderly during 3 meetings Result: From the results of measuring the knowledge of the elderly in the prolanis group at the Tajinan District Health Center. In Malang, data was obtained that there was an increase in the average pretest and posttest scores, the average pretest knowledge results of respondents were in the poor category. At the end of the evaluation activity, the average posttest results of respondents' knowledge were in the sufficient category. The ability of the elderly in the prolanis group at the Tajinan District Health Center. Malang, to demonstrate brain exercise modality therapy to improve the cognitive function of the elderly, obtained the average value of the results of the respondents' ability to re-demonstrate in the sufficient category Conclusion: It can be concluded that the aim of the training is to increase the knowledge and understanding of the elderly in the prolanis group regarding Brain Gym exercises to improve the cognitive function of the elderly can be achieved.